Exploring Environments through Water: An Ethno-Hydrography of the Tibesti Mountains (Central Sahara) - Musch, Tilman (Ethnobiology Letters, 2021)
An ethno-hydrography, studying the organization of space through water, can provide a key to understanding how people conceive their environments in a holistic way. Based on mapping as a dynamic process, different representations of river systems among the Tubu Teda, who live in the Tibesti mountains (Central Sahara), are described in this paper. I first discuss a large-scale subdivision of the mountains into drainage basins, and then representations of a sub-regional and local river system, including an engraving on a sandstone rock. Finally, I discuss these case studies in the context of holistic experiences of environments and the dynamic processes of mapping.